Politeness Strategies Performed by EFL Learners’ with English Native Speakers in Medical Students - Sri Rejeki; Alfi Nur Azizah (Bina Nusantara University, 2019)
The purpose of the research was to find out what politeness strategies used by EFL learners when they are having a conversation with English native speakers and the factors for selecting these particular strategies. The research applied a descriptive qualitative research. The participants were 28 non-English major (medical students) students in the first semester. The instrument of the research was data from videos presenting students’ conversation with english native speakers. They were analyzed by using Brown and Levinson categories of politeness. The result shows that the learners use three among four politeness strategies proposed by Brown and Levinson namely positive, negative, and off-record strategies. The positive politeness strategies become the most widely used ones.